PENGARUH PROGRAM KREDIT USAHA RAKYAT (KUR) PT. BANK RAKYAT INDONESIA UNIT TELUK PANJI TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI DESA TELUK PANJI KECAMATAN KAMPUNG RAKYAT KABUPATEN LABUHANBATU SELATAN - Frenky Tanni Wijaya (Welfare StatE, 2013)
One task of the State is to create a just and prosperous society . Developing countries one of Indonesia , in general, has a population of many , potentially still have to be developed further in order to be authorized effective development . Indonesia is a country with abundant natural resources , Indonesia's natural wealth is spread all over the country . But in fact the potential of Indonesia was not able to address the social and economic problems of this nation . The problems that occurs is , the uneven development and economic gap between communities cause poverty. The government created several programs to alleviate poverty . One of them is the Kredit Usaha Rakyat Program. The purpose of this study was to determine the effect of Kredit Usaha Rakyat Programs of PT.BRI on socio-economic life, benefits of this research are expected to be useful for the implementation of the model development program in particular the Government of the People's Business Credit. This research method using explanative type , specifically the research that was conducted in order to test or prove the hypothesis . The research was conducted in the Teluk Panji Village Kampung Rakyat District Regency of Labuhanbatu Selatan with a total sample of 79 people. Techniques of data collection through questionnaires to the people who receive the program 's Kredit Usaha Rakyat (KUR ) . The data were tabulated into tables and process the data further analyzed quantitatively by simple linear regression analysis , and t - test statistics and Test F. Based on the analysis it can be concluded that, it can be concluded that the Kredit Usaha Rakyat Program has an influence on the socio-economic life of the people in Teluk Panji Village . R - Square value of 0.079 indicates the influence 7,9 % . T test and F test showed that significantly influence the simultaneous partial and Community Socioeconomic life .Effect of views based on economic conditions , employment , education and health Keywords : Effect, Public Credit , Social Economy , Society